Analisis Konseling Resiprokal untuk Meningkatkan Sensitifitas Gender Pada Pasangan Suami Istri : (Kajian Bimbingan Konseling Islam Faqihuddin Abdul Kodir) (Jurusan Bimbingan dan Konseling Islam, 2017)
This research is motivated by an annual record conducted by the National Commission on Violence Against Women from 2005 to 2009 which illustrates a significant increase each year. Starting from this fact, it is necessary to protect women and prevent domestic violence through counseling guidance. This research method is a qualitative method that aims at exploration and verification. In this study data were obtained through interviews, documentation, observation, and counseling. Presentation and analysis of data is done by descriptive analytic. The study concluded that the counseling guidance conducted by Faqihuddin Abdul Kodir was relevant to the foundation and principles of Islamic counseling guidance. Then found the basic concept of counseling is; a) marriage as a contract of authority not a contract of ownership, b) relationships are built with the aim of creating mutual prosperity and avoiding harm, c) good relations and reciprocal relations. The counseling model used is to use a gender equality paradigm, goal-oriented, reciprocal relations between partners, and flexible interactions between counselor and client. The counseling process is carried out by mediating counselees who have differences in child care patterns and relationship mismatches. Interventions were conducted with counseling interviews using guidelines developed in accordance with framing techniques. Until the results reciprocal counseling to increase gender sensitivity in married couples succeeded effectively.